Pemetaan Sarana dan Prasarana Objek Geowisata Batu Angus di Kecamatan Tarnate Barat Provinsi Maluku Utara - Robo, Sarif; Tangge, Nurul Ainun (Journal of Tourism and Creativity, 2024)
Batu Angus Geotourism in West Ternate District, North Maluku, is one of the popular tourist destinations in Indonesia that offers unique and interesting natural scenery. The area is famous for its black volcanic rocks and rough texture, the result of an ancient volcanic eruption. This study aims to map the facilities and infrastructure at the Batu Angus Geotourism Object in the Kulaba Village, West Ternate District using a GIS application in order to map the location and area of facilities and infrastructure, analyze the condition of facilities and infrastructure, and provide recommendations for development facilities and infrastructure at the Batu Angus Geotourism Object. The method used is a spatial approach based on a geospatial information system by means of field surveys to collect spatial data on the location and area of facilities and infrastructure, interviews with tourist attraction managers and tourists to collect attribute data on the condition of facilities and infrastructure, and documentation to collect secondary data in the form of photos and maps. The results of the study showed that the condition of the facilities and infrastructure was adequate, including a parking area, stage, gazebo, and toilets. Facilities that need to be improved include clean water, electricity, a museum, and road access. Mapping was carried out using the ArcGIS application to produce a digital map of the distribution of facilities and infrastructure. This map helps tourists to find available facilities. Batu Angus Geotourism has great potential to be developed. It is necessary to improve facilities and infrastructure, tourism promotion, and public awareness to support the development of this tourism.